Readiness for AI adoption of Philippine business and industry: The government's role in fostering innovation- and AI-driven industrial development - Francis Mark A. Quimba; Neil Irwin S. Moreno; Alliah Mae C. Salazar (Philippine Institute for Development Studies (PIDS), 2024)
This paper examines the current state of AI adoption in Philippine businesses and industries, analyzing the barriers to adoption and evaluating the government's role in fostering AI-driven industrial development. Through analysis of various AI readiness indices and case studies, the research finds that while basic digital infrastructure is widespread, with 90.8 percent of establishments having computers and 81 percent having internet access, advanced technology adoption remains limited. Only 14.9 percent of firms use AI technologies, with adoption concentrated in urban areas and larger firms, particularly in the ICT and BPO sectors. The study identifies key barriers including limited digital infrastructure, low awareness of AI technologies, significant skills gaps, and insufficient funding opportunities. Drawing from economic theory and international case studies, the paper outlines three critical domains for government intervention: market facilitation, capability building, and ecosystem coordination. The research proposes policy recommendations focusing on infrastructure development, human capital development, regulatory frameworks, public-private partnerships, and ethical guidelines. These recommendations emphasize the need for coordinated action across government agencies, substantial investment in digital infrastructure and education, and the establishment of clear governance frameworks to ensure responsible AI adoption while fostering innovation and competitiveness in the Philippine business sector.
Keywords: 330; artificial intelligence; AI policy; industrial policy; AI adoption